ANALISIS SINGLE INDEX MODEL DALAM PEMBENTUKAN PORTOFOLIO OPTIMAL (STUDI SAHAM INDEKS LQ45 PERIODE 2017–2022) - Jabida Latuamury (JURNAL LENTERA AKUNTANSI, 2022)
This study examines the optimal portfolio composition of stocks and calculates the return and risk of the optimal portfolio formed using a single index model. The type of research used in this study is descriptive research with a quantitative approach. This research uses secondary data in the form of stock prices for the 2017-2022 period. The data analysis method used is stock analysis with a single index model. The results showed five stocks from 29 stock samples, including the optimal portfolio. Here are the optimal portfolio stocks and their composition: ADRO at 4.41%, ANTM at 10.02%, BBCA at 54.33%, BBRI at 8.65%, and CPIN at 22.59%. The portfolio formed will generate an expected portfolio return of 1.72% and a portfolio risk level of 1.20%.Key words: Expected Return, Optimal Portfolio, Risk, Single Index Model